2021
DOI: 10.3390/jimaging7030041
|View full text |Cite
|
Sign up to set email alerts
|

A Cortical-Inspired Sub-Riemannian Model for Poggendorff-Type Visual Illusions

Abstract: We consider Wilson-Cowan-type models for the mathematical description of orientation-dependent Poggendorff-like illusions. Our modelling improves two previously proposed cortical-inspired approaches, embedding the sub-Riemannian heat kernel into the neuronal interaction term, in agreement with the intrinsically anisotropic functional architecture of V1 based on both local and lateral connections. For the numerical realisation of both models, we consider standard gradient descent algorithms combined with Fourie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 69 publications
(153 reference statements)
2
10
0
Order By: Relevance
“…Simple cell receptive profiles can be modeled in terms of Gabor functions [33,41,55,57]. In the orientation, frequency and phase selective model framework, the receptive profile of a simple cell is a Gabor function of the following type:…”
Section: Feature Value Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple cell receptive profiles can be modeled in terms of Gabor functions [33,41,55,57]. In the orientation, frequency and phase selective model framework, the receptive profile of a simple cell is a Gabor function of the following type:…”
Section: Feature Value Extractionmentioning
confidence: 99%
“…This framework was extended to higher dimensional geometries where scale [34] and velocity [35,36] were taken into account. Various biologically inspired models for optical illusions [37][38][39][40][41] and orientation preference maps [42], as well as frameworks for image processing [43][44][45][46][47][48][49][50], for pattern recognition [51] and for medical applications [52,53], were proposed in the sub-Riemannian geometry of SE (2).…”
Section: Introductionmentioning
confidence: 99%
“…Simple cell receptive profiles can be modeled in terms of Gabor functions [33,41,54,57]. In the orientation, frequency and phase selective model framework, receptive profile of a simple cell is a Gabor function of the following type:…”
Section: Feature Value Extractionmentioning
confidence: 99%
“…This framework was extended to higher dimensional geometries where scale [34], and velocity [35,36] were taken into account. Various biologically-inspired models for optical illusions [37][38][39][40][41] and orientation preference maps [42], as well as frameworks for image processing [43][44][45][46][47][48][49], for pattern recognition [50] and for medical applications [51,52], were proposed in the sub-Riemannian geometry of SE (2).…”
mentioning
confidence: 99%
“…First, the organization of visual data based on their location and orientation [Hubel and Wiesel, 1962] is modeled by Lie group convolutions [Bekkers, 2019], in which feature maps encode response for every position and every orientation. Second, long-range interactions between aligned neurons [Bosking et al, 1997] are modeled by building graphs with affinity matrices based on (approximate) sub-Riemannian distances on the Lie groups, inspired by sub-Riemannian image analysis methods such as [Franken and Duits, 2009, Favali et al, 2016, Mashtakov et al, 2017, Boscain et al, 2018, Duits et al, 2018, Baspinar et al, 2021. Defferrard et al [2020] showed how to construct powerful graph NNs that are faithful to the manifolds on which they are defined.…”
Section: Introductionmentioning
confidence: 99%